Biomechanical three-dimensional finite element analysis of single implant-supported prostheses in the anterior maxilla, with different surgical techniques and implant types - Verri, Fellippo Ramos [UNESP]; Santiago, Joel Ferreira; Almeida, Daniel Augusto Faria; Batista, Victor Eduardo de Souza [UNESP]; Lemos, Cleidiel Aparecido Araujo [UNESP]; Mello, Caroline Cantieri [UNESP]; Pellizzer, Eduardo Piza [UNESP] (Quintessence Publishing, 2017)
Purpose: The aim of this study was to use three-dimensional finite element analysis to analyze the stress distribution transferred by single implant-supported prostheses placed in the anterior maxilla using different connections (external hexagon, internal hexagon, or Morse taper), inclinations of the load (0, 30, or 60 degrees), and surgical techniques for placement (monocortical/conventional, bicortical, or bicortical with nasal floor elevation). Materials and Methods: Nine models representing a bone block of this region were simulated by computer-aided design software (InVesalius, Rhinoceros, SolidWorks). Each model received one implant, which supported a cemented metalloceramic crown. Using FEMAP software, finite elements were discretized while simulating a 178-N load at 0, 30, and 60 degrees relative to the long axis of the implant. The problem was solved in NEi Nastran software, and postprocessing was performed in FEMAP. Von Mises stress and maximum principal stress maps were made. Results: The von Mises stress analysis revealed that stress increased with increasing inclination of the load, from 0 to 30 to 60 degrees. Morse taper implants showed less stress concentration around the cervical and apical areas of the implant. The bicortical technique, associated or not with nasal floor elevation, contributed to decreasing the stress concentration in the apical area of the implant. Maximum principal stress analysis showed that the increase in inclination was proportional to the increase in stress on the bone tissue in the cervical area. Lower stress concentrations in the cortical bone were obtained with Morse taper implants and the bicortical technique compared with other connections and surgical techniques, respectively. Conclusion: Increasing the inclination of the applied force relative to the long axis of the implant tended to overload the peri-implant bone tissue and the internal structure of the implants. The Morse taper connection and bicortical techniques seemed to be more favorable than other connections or techniques, respectively, for restoring the anterior maxilla.
Keywords: Dental implant; Finite element analysis; Mechanical stress